Hierarchical representation of species distributions for biological survey and monitoring - Stoms, D. M.; Davis, F. W.; Hollander, A. D. (GIS and Environmental Modeling: Progress and Research Issues, 1996)
Spatial and temporal axes of domain, grain, and sampling intensity can serve as a framework to discuss opportunities for integrating spatial biodiversity data into richer, more complex representations of species distributions. This conceptual framework also highlights many of the problems in integrating data of different spatial, temporal and thematic properties. A recent analysis of the distribution of the orange-throated whiptail lizard in southern California is reviewed as an example of integration of datasets. Comparison of representations resulting from different data sources makes biases evident, highlights areas of inadequate sampling, and can lead to new inferences about habitat relationships through convergence of evidence. Improvements in the technology needed to facilitate better integration of distribution models with GIS in the areas of data entry, linkages to tools outside traditional GIS functionality, and new GIS tools to integrate existing datasets are discussed.
Keywords: data hypercube; GIS modeling; orange-throated whiptail